A contribution to peace policy - Hans Matthöfer (Intereconomics, 1979)
A fresh start is needed in development policy in order to move away from the sort of superficial, overselective assistance, which is very often altruistic in appearance only, towards a more comprehensive, world-wide structural policy which does not only raise more resources for setting up a productive economy in the Third World, but also combats poverty at its very roots.
Keywords: 330; Development Policy